Limitation of Public Service Special Assignment Charges Bond in the Form of a BUMN Persero (State-Owned Enterprises) - Arya Anggara (Perantara Law Review, 2024)
This study analyzes the limitations of charging Public Service Obligation (PSO) fees on State-Owned Enterprises (BUMN) in the form of Persero in Indonesia, which until now has not been specifically regulated in the law. PSO is only mentioned in the clause "considering the intent and purpose of BUMN," which triggers challenges in its implementation without sacrificing the efficiency and profitability of Persero. This study uses a normative legal method, focusing on the study of laws and regulations and legal principles governing the management of BUMN and its role in supporting public policy, with the results showing that the imposition of PSO on BUMN Persero is based on two legal ratios: legal-philosophical and sociological. The legal-philosophical reason comes from the mandate of Article 34 paragraph (3) of the 1945 Constitution, which emphasizes the role of the state in improving the welfare of the community through public services. The sociological reason reflects the role of BUMN as a government tool to help the state achieve its goals. realizing welfare through basic services, where Persero can play a flexible role as an agent of public policy. This study recommends the establishment of a more detailed legal framework to regulate PSO cost limits for BUMN Persero, so that PSO can be implemented proportionally, support the economic balance of BUMN, and provide benefits to the wider community.